Impact of inter-urban street lighting on users perception of road safety behavior: A Case of Jalan Majalengka-Rajagaluh - Nuri Sumantri, Vena; Rifai, Andri Irfan; Ferial, Ferial (DAS Institute, 2022)
Road lighting is one of the main things needed by road users to improve safety when driving at night. However, frequently road lights that meet the standards are only on large-scale roads. On the other hand, in general, road users in Majalengka tend to use high speeds. Based on this, this study aims to analyze the impact of lighting on the safety of road users in Jalan Majalengka-Rajagaluh. The research method used in this study is a perceptual analysis method. The results show an average value of road lighting importance is 9.47, the average satisfaction is 6.12, and the average gap is -3.35. Many variables are in quadrant IV, which indicates that many variables still require more concentration to increase. Therefore, according to road users' perception, road lighting is considered essential in various aspects, but road users still feel it is necessary to improve road lighting performance.